Augmenting Consumer Acceptance of Robot-Assisted Technologies in Retail Industry: An Interdisciplinary Approach - M, Khalufi Nasser Ali (STIE Malangkucecwara, 2024)
Since they have been incorporated into retail, robots have been discussed more frequently in academic publications and public debate. Customers in retail sector, as well as workers will be resistant to the rising employment of robots as their capabilities increase and they are employed to supplement or replace human labour.